The effects of applying an augmented reality English teaching system on students’ STEAM learning perceptions and technology acceptance - Su, Yu-Sheng; Lai, Chieh-Chun; Wu, Ting-Kai; Lai, Chin-Feng (Frontiers in Psychology, 2022)
English has now become one of the necessary abilities for connecting with the world, and this study builds upon the framework of STEAM, combining it with Augmented Reality (AR) technology to integrate gaming into the learning of English. With the inherent interdisciplinary and hands-on nature of the STEAM system, we plan to change the way the English language is taught, no longer confining it to monotonous tests and dull textbooks. Teaching in AR tends to pique interest within students, making them more willing to participate in learning. This study uses AR in conjunction with gaming, where the participants will be split into pairs, which promotes friendly competition amongst themselves, and in turn drive them to learn more. We also added the ability to track their own performance, as well as an in-depth explanation for every question. We plan to integrate this system into the curriculum is that the teachers will still teach like they used to, but use our system as a tool to help make lessons more fun and enjoyable. To help us find potential oversights and check on how people feel about this study, we put out surveys regarding STEAM learning and the overall ease of use. The results showed that not only is AR English learning widely considered helpful by students, our system was also easy to operate, and that competing with peers really motivated them to do better.